Postcolonial Muslim Women between Faith and Fashion in Habib Selmi´s Novel “The Women of al-Basatin"(2010) - Alsiefy, Amany A. (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: This paper traces the widespread wave of fashionable headscarf- wearers (hijabs) in Muslim societies in an attempt to illustrate how the contemporary spirit of consumer culture informs female´s self-image and behaviour in the context of post-colonial literature. I am going to do that concerning the voices of the fictional female figures in Habib Al-Selmi´s novel "The Women of al-Basatin (2010) Habib Salmi is a renowned Arab writer whose modern Arabic literature explores the relationship/ clash between Eastern and Western values. In this paper, I aim to highlight the meanings attributed to this practice of head-covering as in contemporary consumerist Tunisian society individually, culturally and contextually assigned.